SELF EFFICACY, SELF CARE MANAGEMENT, DAN KEPATUHAN PADA LANSIA HIPERTENSI (STUDI FENOMENOLOGI) - Ninda Ayu Prabasari (Jurnal Keperawatan Malang, 2021)
Background: Long suffering, lack of knowledge, the level of boredom with therapy makes the elderly are not compliant in treatment, do not have good confidence and lack of self-care management, causing further complications. Self-efficacy is a dominant factor and an important predictor of managing hypertension in medication adherence through self-care management. Self-efficacy will affect thinking, feeling, motivating yourself and acting on elderly hypertension. Objectives: objective of the study is to obtain data by exploring self-efficacy, self-care management, and adherence to elderly hypertension Methods: This study used qualitative method with a phenomenological approach. The study population was elderly hypertension aged ? 60 years who were undergoing treatment at Posyandu Lansia Sekar Arum RW VII Kertajaya Sub-District, Gubeng Sub-District Surabaya as many as 5 participants who were obtained through purposive sampling. Data collection was carried out by interview analyzed using Collaizi method. Results: The results showed 9 themes, namely the Concept of Self Efficacy, the Concept of Self Care Management, the Concept of Compliance, Response to Disease, Confidence in the effectiveness of therapy, Management of hypertension therapy, supporting factors, inhibiting factors, Quality of life. Conclusion: Elderly hypertension quality life is determined by self-efficacy, self-care management and adherence to treatment process which is undertaken. Primary health care center should be able to improve the quality of life of the elderly by continuing to provide support to elderly hypertension through ongoing health education programs. Keywords: Self Efficacy, Self-Care Management, Compliance, Elderly, Hypertension